A Facile Synthesis and Studies of Some New Chalcones and Their Derivatives Based on Heterocyclic Ring. Issue 4 (2012) - Solankee, A.; Patel, K.; Patel, R.
Abstract : Chalcones (6a-f) have been prepared by the condensation of ketone (5) and different aromatic and heterocyclic aldehydes. These chalcones (6a-f) on treatment with guanidine hydrochloride and phenyl hydrazine hydrochloride in presence of alkali give aminopyrimidines (7a-f) and phenylpyrazolines (8a-f) respectively. All the newly synthesized compounds have been characterized on the basis of IR, 1 HNMR spectral data as well as physical data. Antibacterial activity (minimum inhibitory concentration MIC) against Gram-positive S. aureus MTCC 96 and S. pyogeneus MTCC 442 and Gram-negative P. aeruginosa MTCC 1688 and E. coli MTCC 443 bacteria, as well as antifungal acivities (MIC) against C. albicans MTCC 227, A. niger MTCC 282 and A. clavatus MTCC 1323 were determined by broth dilution method.